Influence of institutional pressure and ownership structure on corporate social responsibility disclosure - Darus, Faizah; Arshad, Roshayani; Othman, Suaini; Jusoff, Kamaruzaman (Institute of Interdisciplinary Business Research, 2009)
A clear understanding of the effectiveness of regulation is crucial to regulatory bodies in their efforts to improve corporate transparency. This study examines the effects of the introduction of regulatory requirements relating to Corporate Social Responsibility (CSR) disclosure, and the impact of institutional pressure and ownership structure on management’s disclosure decisions. Using the annual reports of 144 Malaysian listed companies, this study investigates the effects of regulatory efforts in promoting CSR disclosure in periods of uncertainty before (2005 and 2006) and with the introduction of regulatory requirements (2007), and the association of ownership structure on the extent of CSR disclosure. The regulatory disclosure environment, managers’ imitation strategy through board interlock and ownership structure (proxy by family, government and foreign ownerships) relating to CSR disclosure were investigated. Results of this study provide evidence that regulatory efforts are important mechanism in promoting greater corporate transparency in CSR disclosure. This is reflected in the significant association between government ownership and the extent of such disclosure. However, the findings demonstrate that such efforts do not appear to promote disclosures of CSR activities in family owned companies. Nevertheless, the findings indicate strong possibility of raising investors and other stakeholders’ expectations towards expecting more detailed disclosure of CSR activities in companies’ annual reports through the influence of regulatory efforts. An implication of these findings is that regulatory efforts have the prospect of becoming a significant force in promoting the extent and quality of CSR disclosure.